Pioneers and partisans : an oral history of Nazi genocide in Belorussia - Walke, Anika (The Oxford oral history series, 2015)
"Thousands of young Jews were orphaned by the Nazi genocide in the German-occupied Soviet Union and struggled for survival on their own. This book weaves together oral histories, video testimonies, and memoirs produced in the former Soviet Union to show how the first generation of Soviet Jews, born after the foundation of the USSR, experienced the Nazi genocide and how they remember it in a context of social change following the dissolution of the USSR in 1991. The 1930s, a period when the notions of interethnic solidarity and social equality were promoted and a partly lived reality, were formative for a cohort of young Jews. Soviet policies of the time established a powerful framework for the ways in which survivors of the genocide understood, survived, and represent their experience of violence and displacement. The book demonstrates that the young Soviet Jews' struggle for survival, and its memory, was shaped by interethnic relationships within the occupied society, German annihilation policy, and Soviet efforts to construct a patriotic unity of the Soviet population. Age and gender were crucial factors for experiencing, surviving, and remembering the Nazi genocide in Soviet territories, an element that Anika Walke emphasizes by investigating the individual and collective efforts to save peoples' lives, in hiding places and partisan formations, and how these efforts were subsequently erased in the construction of the Soviet war portrayal. Pioneers and Partisans demonstrates how the Holocaust unfolded in the German-occupied Soviet territories and how Soviet citizens responded to it. The book does this work through oral histories of atrocities and survival during the German occupation in Minsk and a number of small towns in Eastern Belorussia such as Shchedrin, Slavnoe, Zhlobin, and Shklov. Following particular individuals' stories, framed within the broader historical and cultural context, this book tells of repeated transformations of identity, from Soviet citizen in the prewar years, to a target of genocidal violence during the war, to barely accepted national minority in the postwar Soviet Union"--